Reinterpreting Indonesian Folklore in EFL Education: Symbolic Meaning, Local Wisdom and Generation Z Perspectives - Andi Irlina; Hidayah Nor; Thaibatun Nisa (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2026)
This qualitative study explores how Indonesian local folklore can function as a literary and pedagogical resource in English as a Foreign Language (EFL) education by examining symbolic meanings, educational values, and generational reinterpretation. Focusing on the legends of Princess Mayangsari from the Banjar community and Princess Tadampalik from the Bugis tradition, the study integrates Symbolic Interactionism and Value Theory (Western and Islamic) to analyze how moral, cultural, and spiritual values are constructed and transformed. Data were collected through content analysis and in-depth interviews with 20 Generation Z participants, and analyzed using thematic coding. The findings reveal that traditional symbols such as the sacred sword, mirror, white buffalo, and heirloom kris are reinterpreted by Generation Z within contemporary frameworks of rationality, gender equality, ethical leadership, and digital creativity. Rather than perceiving folklore as sacred and static, participants engage with these narratives as reflective texts that support identity formation and moral reasoning. From an EFL perspective, the study demonstrates that local folklore provides authentic narrative materials that enhance narrative literacy, cultural awareness, and character education. The integration of symbolic analysis and digital storytelling further highlights the potential of folklore-based pedagogy to support critical reading, interpretation, and intercultural competence in language learning contexts.